Reversal of L Phase by Slow Inactivation of Penicillin with Polyamines - Lapinski, E. M. (1970)
Spermine reversal of penicillin-induced L phase of Haemophilus was found to be due to slow inactivation of penicillin by spermine. This inactivation was inhibited by sodium chloride. Cycloserine and cephalothin were also inactivated by spermine as demonstrated by reversal of L phase induced by these antibiotics. Spermine was inhibitory for growth of L phase induced by glycine. Spermidine and the diamines, putrescine and cadaverine, also interacted with penicillin, but very slowly and only at high molar ratios of polyamine to penicillin.